Instrumental insemination and reproductive incompatibility between the European honeybee, Apis mellifera and Asian honeybee species - Mananya Phiancharoen; Siriwat Wongsiri (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2003